Multimodality imaging in evaluation of cardiac masses - Sihotang, Fransiska Anggreni; Handari, Saskia Dyah (Universitas Brawijaya, 2025)
Cardiac masses are infrequently encountered in routine cardiology practice but often pose as a diagnostic challenge. Cardiac masses can be categorised as either neoplastic (benign and malignant) or non-neoplastic, and as either primary or secondary. The prognosis is contingent upon the identification of the mass, as treatment choices vary significantly. Histopathology remains the most dependable approach for diagnosing any cardiac tumour. Nevertheless, given its invasive characteristics, cardiac imaging plays a crucial role in diagnosing cardiac masses. The emergence of new imaging tools necessitates a multimodality strategy to assess intracardiac masses. This approach is crucial for non-invasive evaluation before considering surgical planning or oncological treatment. This article aims to compare the different imaging techniques, particularly echocardiography, cardiovascular magnetic resonance, cardiac computed tomography, and nuclear imaging, in terms of their clinical applications in the evaluation of cardiac masses and to determine distinctive features on these modalities for the most prevalent intracardiac masses.